A method for producing a liquid metal thermoplastic polyurethane-spandex laminate composite
Patent Information
- Application Number
- CN202611163249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明提供了一种兼具吸收型电磁屏蔽与拉伸传感功能的液态金属热塑性聚氨酯-氨纶叠层复合材料的制备方法,具体解决以下三个关键技术问题:
[0038](1)分散稳定性显著提升,通过引入多酚类物质与Ga3+的螯合作用,在LM表面原位形成致密Ga2O3壳层,无需额外表面活性剂即可实现LM在有机溶剂中的长期稳定分散,且分散液可存放数天无明显再聚。
Smart Images

Figure CN122956738A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a method for preparing a liquid metal / thermoplastic polyurethane-spandex laminate composite material that combines absorption-type electromagnetic shielding and tensile sensing functions. This composite material integrates a gallium-based liquid metal network dispersed with polyphenols and a conductive spandex fabric reduced in situ with silver ions via hot-melt adhesive interface, achieving the dual functions of absorption-dominant electromagnetic shielding and stable resistance-strain sensing. Background Technology
[0002] With the rapid development of wearable electronic devices and flexible sensors, especially the emergence of new application areas such as electronic skin, soft robots, human-computer interaction systems, and intelligent medical and health monitoring, the demand for lightweight, stretchable composite materials that combine electromagnetic compatibility (EMC) protection and mechanical sensing functions is becoming increasingly urgent. For example, in the application of "electronic skin" that gives soft robots tactile perception, the material not only needs to have high flexibility and accurate strain sensing capabilities to adapt to complex human movements or mechanical deformations, but also needs to have excellent electromagnetic shielding performance to ensure that the sensor is protected from external signal interference in complex electromagnetic environments and does not generate electromagnetic pollution for surrounding precision electronic components. Gallium-based liquid metal (LM) is considered an ideal flexible conductive filling phase due to its ultra-high conductivity, intrinsic deformability, and low Young's modulus. However, liquid metal faces two major bottlenecks in practical applications: first, it is very easy to re-agglomerate in polymer matrices, making it difficult to achieve uniform and stable micro-nano dispersion; second, under repeated deformation, liquid metal is prone to leakage or migration from the matrix to the surface, leading to conductive network failure, short circuits, or contamination.
[0003] In existing technologies, a common strategy is to disperse LM in an organic solvent using high-intensity ultrasound before incorporating it into the elastomer. However, ultrasound alone cannot completely suppress droplet re-agglomeration, especially at high LM contents or during long-term storage. Furthermore, to improve dispersion stability, researchers have attempted to introduce surfactants or coating layers, but most approaches increase process complexity or reduce the continuity of the conductive network. On the other hand, to achieve tensile sensing, conductive fillers such as silver nanowires and carbon nanotubes are often attached to the elastomer surface. However, these rigid fillers are prone to breakage or detachment under repeated stretching, and when coexisting with the LM layer, they are susceptible to interfacial migration or alloying, affecting device reliability.
[0004] Currently, there is no method that can simultaneously solve the problems of stable dispersion, leakage prevention, and functional decoupling between the sensing electrode and the shielding layer of liquid metal composites. This greatly limits the large-scale application of liquid metal composite materials in high-end flexible sensing, biomimetic robotics, and other fields. This invention proposes an integrated solution to address the aforementioned technological gaps. Summary of the Invention
[0005] This invention provides a method for preparing a liquid metal thermoplastic polyurethane-spandex laminate composite material that combines absorption-type electromagnetic shielding and tensile sensing functions, specifically addressing the following three key technical problems:
[0006] (1) How to achieve long-term stable dispersion of gallium-based liquid metal in organic solvents without introducing additional surfactants, and suppress its re-agglomeration in thermoplastic polyurethane elastomer (TPU) matrix.
[0007] (2) How to construct a sensing electrode layer that is electrically isolated and mechanically conformal to the LM / TPU layer to avoid short circuits and signal drift caused by LM migration.
[0008] (3) How to integrate the shielding layer and the sensing layer through a simple lamination process while maintaining the overall flexibility, stretchability and electromagnetic shielding absorption characteristics.
[0009] The specific technical solution of this invention is as follows:
[0010] First, the present invention provides a method for preparing a liquid metal thermoplastic polyurethane-spandex laminated composite material, which includes the following steps:
[0011] S1. Add gallium-based liquid metal and polyphenols containing catechol and / or trihydroxyl groups to an organic solvent, and disperse by ultrasonication, so that the polyphenols react with the Ga... 3+ Chelating coordination promotes the formation of gallium oxide shells, resulting in a stable liquid metal dispersion.
[0012] S2. Mix the liquid metal dispersion with the thermoplastic polyurethane elastomer (TPU) masterbatch, stir evenly, pour into a mold to form a liquid metal / TPU film.
[0013] S3. Construct an adhesive layer containing catechol groups on the surface of spandex, and then place it in a solution containing silver ions to in-situ reduce and deposit silver nanoparticles to obtain conductive modified spandex.
[0014] S4. The liquid metal / TPU film is hot-pressed with conductive modified spandex to form an integrated liquid metal thermoplastic polyurethane-spandex laminated composite material.
[0015] The technical concept of this invention is: utilizing polyphenolic substances containing catechol / trihydroxyl groups (such as gallic acid, lignin, dopamine, tannic acid) and Ga 3+The strong chelating coordination effect of the LM promotes the in-situ formation of a dense gallium oxide (Ga2O3) shell on the LM surface during ultrasonic dispersion. This shell inhibits the re-agglomeration of LM droplets through steric hindrance and electrostatic repulsion, and provides active sites for subsequent interfacial bonding with the TPU matrix. Simultaneously, the electromagnetic shielding function and tensile sensing function are physically decoupled in layers: the LM / TPU layer provides absorption-type electromagnetic shielding and mechanical support, while the PDA-Ag nanoparticle conductive layer on the spandex substrate functions as the sensing electrode. The two are firmly bonded and electrically isolated through an interface layer (e.g., a hot melt adhesive layer), preventing LM migration across layers. In the construction of the sensing layer, this invention employs an adhesive layer containing catechol groups and an in-situ reduction strategy using a silver ion solution, preserving the operability and universality of the process.
[0016] Preferably, in S1, the polyphenolic substance is one or more of gallic acid, lignin, dopamine, or tannic acid; more preferably, it is one or more of gallic acid and lignin.
[0017] Under ultrasonic dispersion, polyphenol molecules undergo strong chelation coordination with Ga2O3 generated on the liquid metal surface, forming a "gallium oxide / polyphenol" organic-inorganic composite shell on the particle surface. This core-shell structure provides strong steric hindrance and electrostatic repulsion, preventing the liquid metal from fusing into a large metal network. Instead, it remains uniformly suspended in the solvent as independent single particles, allowing it to be uniformly dispersed in the TPU matrix.
[0018] This invention has found that the types of polyphenols have a significant impact on the performance of composite materials: (1) In terms of liquid metal dispersion and electromagnetic absorption behavior: gallic acid, lignin, and dopamine can efficiently react with Ga 3+ Coordination forms small and uniformly distributed single particles. These single particles are dispersed in the TPU matrix, which can construct a better impedance matching interface and have high absorption characteristics. However, the absorption shielding performance of tannic acid is inferior to that of the other three polyphenols. This may be because the molecular weight of tannic acid is too large and the steric hindrance is too strong, making it difficult to form single particles with uniform particle size, resulting in uneven micro-area dispersion. (2) In terms of strain sensing performance: By adding polyphenols to uniformly dispersed single-particle liquid metal, the tunneling distance and contact state between particles change sensitively during the strain process. Gallic acid and lignin show a wider detection range and higher sensitivity. However, the particle dispersion uniformity is worse when dopamine and / or tannic acid are used, which makes the effective conductive network of the sensor easily destroyed in advance during the stretching process, narrowing the strain range and reducing the sensitivity.
[0019] Preferably, in S1, the gallium-based liquid metal is one or more of gallium-indium alloy, gallium-indium-tin alloy, or gallium-tin alloy; more preferably, it is one or more of gallium-indium alloy or gallium-indium-tin alloy.
[0020] This invention also found that different types of liquid metals have a significant impact on the performance of composite materials: (1) In terms of shielding performance: when gallium-indium alloy and gallium-indium-tin alloy are used, gallium-based metals containing indium have a low melting point and good fluidity at room temperature, which can work synergistically with polyphenols to form small and uniformly distributed single particles. They can build a better impedance matching interface in the TPU matrix, achieve a high absorption coefficient, and exhibit excellent high absorption characteristics. However, when gallium-tin alloy is selected, the absorption and shielding performance of the composite material prepared by dispersion is significantly inferior to that of the other two indium-containing liquid metals. This may be because gallium-tin alloy has poor interfacial tension and wettability, and insufficient coordination stability with lignin. It is difficult to disperse into uniform and stable single particles under ultrasound, resulting in local agglomeration in the micro-region, which destroys the electromagnetic impedance matching of the surface layer. (2) In terms of strain sensing performance: when gallium indium alloy is selected, it exhibits the widest detection range and the highest sensitivity (GF = 6.8); when gallium indium tin alloy is selected, it also has excellent sensing response; however, when gallium tin alloy is selected, due to the poor particle dispersion uniformity, micro-area agglomeration is easily generated, which leads to the premature destruction of the effective conductive network of the sensor during the stretching process, narrowing the strain range and reducing the sensitivity.
[0021] Preferably, in S1, the organic solvent is one or more of N,N-dimethylformamide (DMF), tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), acetone, or butanone; more preferably, it is one or more of N,N-dimethylformamide (DMF), tetrahydrofuran (THF), or butanone.
[0022] The present invention further discovers that different types of solvents also have a significant impact on the performance of composite materials. This is because the polarity and solubility of the solvent not only determine the dispersion effect of polyphenols, but also directly affect the compatibility of liquid metal precursor liquid with TPU matrix and film quality. Specifically: (1) In terms of shielding performance: In water, because TPU is a hydrophobic polymer, it undergoes severe polar phase separation with the aqueous phase, and LM particles cannot be integrated into the TPU matrix, resulting in the inability to form a film. When DMF is selected, it is both an excellent solvent for polyphenols and an excellent solvent for TPU, which can make the LM single particles coated with polyphenols achieve the ultimate uniform dispersion, and can build a better impedance matching interface in the TPU matrix, thereby exhibiting the best high absorption characteristics. Similarly, THF, DMSO and acetone can also effectively dissolve TPU and disperse polyphenols, and the composite materials obtained all exhibit excellent absorption characteristics. (2) In terms of strain sensing performance: In water, the material has no strain sensing performance because it cannot form a film. Organic solvents can be used to achieve a system in which single particles are uniformly dispersed. During the strain process, the tunneling distance and contact state between particles change sensitively.
[0023] DMF exhibits the widest detection range, the highest relative resistance change, and high sensitivity. THF also maintains high sensitivity; however, when choosing DMSO and acetone, the sensing sensitivity decreases due to the different solvent evaporation rates (DMSO evaporates too slowly or acetone evaporates too quickly, resulting in slight differences in the distribution of local particle micro-regions).
[0024] Preferably, in S1, the mass of the polyphenolic substance is 1-10% of the mass of the gallium-based liquid metal.
[0025] The mass percentage of polyphenols also has a significant impact on the performance of composite materials. This is because the amount of polyphenols added directly determines the integrity and thickness of the "gallium oxide / polyphenol" chelate shell on the liquid metal (LM) surface, thereby affecting the dispersion state and interfacial compatibility within the matrix. Specifically: (1) In terms of electromagnetic shielding and mechanical properties: when the proportion of polyphenols is too low, it is insufficient to interact with Ga... 3+ Sufficient chelation, with defects or extremely thin shells, cannot overcome surface tension. LM droplets are prone to secondary fusion to form agglomerates, destroying the dispersion state of single particles, causing electromagnetic impedance mismatch, and the shielding mechanism degenerates into reflection dominance. When the proportion is moderate, an appropriate amount of polyphenols forms a dense and moderately chelated shell, providing perfect spatial steric hindrance to ensure uniform dispersion of LM single particles, constructing an excellent dielectric loss network, and achieving efficient absorption-type electromagnetic shielding. When the proportion is too high, free polyphenols agglomerate in TPU, acting as stress defect points, resulting in a significant decrease in material flexibility, stretchability, and fatigue life. (2) In terms of strain sensing performance: When the proportion of polyphenols is too low, the LM agglomerates in the matrix are prone to stress concentration during stretching, causing irregular changes in the conductive network and severe drift of the resistance-strain response signal. When the proportion is moderate, thanks to the uniformly dispersed system, the tunneling distance between LM particles can undergo stable and sensitive periodic changes during TPU stretching, giving the composite material extremely high sensing sensitivity. When the proportion is too high, the excessively thick insulating layer greatly increases the initial resistance, severely hindering the electron quantum tunneling effect. When stretched, electrons have difficulty penetrating the thick shell to form a conductive path, resulting in a significant decrease in sensitivity or even open circuit failure.
[0026] Preferably, in S1, the mass ratio of the gallium-based liquid metal to the organic solvent is 1:100 to 20:100.
[0027] Preferably, in S1, the ultrasonic pulverization is performed using a cell ultrasonic pulverizer, with an ultrasonic power of 300-700 W and an ultrasonic time of 30-80 min.
[0028] Preferably, in step S2, the gallium-based liquid metal accounts for 1-10% of the mass of the thermoplastic polyurethane elastomer (TPU) masterbatch, and organic solvent is added to make the total solvent amount 2-4 times the mass of the thermoplastic polyurethane elastomer (TPU) masterbatch.
[0029] The mass ratio of gallium-based liquid metal (LM) also has a significant impact on the performance of composite materials because it directly determines the microscopic distribution state, electromagnetic impedance matching characteristics, and interface stability within the matrix. Specifically: (1) In terms of electromagnetic shielding performance: When the ratio is too low, the volume fraction of LM particles is too low and the spacing is too large, making it difficult to form sufficiently dense electric dipoles and micro-interfaces, resulting in extremely limited interface relaxation and dielectric loss, leading to a low absorption coefficient. When the ratio is moderate, the appropriate amount of LM single particles encapsulating polyphenols are uniformly dispersed, forming high-density micro-loss units. This not only achieves perfect surface electromagnetic impedance matching, allowing electromagnetic waves to smoothly enter the interior, but also constructs an "absorption-reflection-reabsorption" path with the reflective layer, causing strong interface polarization and dielectric attenuation, achieving efficient absorption loss. When the ratio is too high, excessive LMs come into contact to form a macroscopic conductive network, causing a surge in surface conductivity and severe impedance mismatch, resulting in a large number of electromagnetic waves being directly reflected on the surface. (2) In terms of mechanics and leak-proof sensing: When the proportion is moderate (1-10%), the LM is completely and tightly covered by the TPU elastomer, which physically prevents leakage or migration during stretching, ensuring the high elasticity and long-term reliability of the material. However, when the proportion is too high (>10%), too many droplets act as phase interface defects, destroying the interaction forces between TPU molecular chains, resulting in a sharp reduction in tensile strength and elongation at break; and during stretching, droplets are very likely to break through the coating layer and leak to the surface, eroding and short-circuiting the spandex sensing layer, leading to serious drift of the sensing signal or even device failure.
[0030] Preferably, in S2, the stirring temperature is 70-90 ℃ and the stirring time is 10-60 min; the thickness of the liquid metal / TPU film is 1-3 mm.
[0031] Preferably, in S3, the adhesive layer containing catechol groups is formed by the oxidative self-polymerization of dopamine hydrochloride in a Tris buffer solution with a pH of 8.0-9.0, the dopamine concentration is 1-4 mg / mL, and the reaction is carried out at room temperature for 12-24 h.
[0032] Preferably, in S3, the silver ion-containing solution is a silver ammonia solution with a concentration of 0.05-0.5 mol / L and an in-situ reduction deposition time of 10-60 min; or the silver ion-containing solution is an AgNO3 complexation system solution with organic acid.
[0033] Preferably, in S3, the reducing agent used for reduction is one of glucose, ascorbic acid, or tartaric acid.
[0034] Preferably, in step S4, the liquid metal / TPU film and the conductive modified spandex are hot-pressed together through an intermediate hot melt adhesive layer; the hot melt adhesive layer is an EVA hot melt adhesive film or a polyurethane hot melt adhesive film with a thickness of 0.05-0.2 mm; the hot pressing temperature is 120-180 ℃, the pressure is 0.5-5 MPa, and the hot pressing time is 1-10 min.
[0035] Secondly, the present invention provides a liquid metal thermoplastic polyurethane-spandex laminated composite material prepared by the above preparation method.
[0036] The composite material of this invention has a three-layer stacked structure of "liquid metal / TPU film - hot melt adhesive interface layer - catechol-containing adhesive layer / silver nanoparticles / spandex". The liquid metal / TPU layer provides absorption-type electromagnetic shielding (A>R) and reversible deformation bearing. The PDA-Ag / spandex layer provides stable surface sheet resistance and an electrode network for resistive tensile sensing; the hot melt adhesive interface layer simultaneously achieves adhesion, stress gradient buffering, and prevention of migration of the liquid metal components.
[0037] Compared with the prior art, the beneficial effects of the present invention are:
[0038] (1) The dispersion stability is significantly improved by introducing polyphenols and Ga 3+ The chelation effect forms a dense Ga2O3 shell on the surface of LM in situ, which can achieve long-term stable dispersion of LM in organic solvents without the need for additional surfactants, and the dispersion can be stored for several days without significant re-aggregation.
[0039] (2) The electromagnetic shielding layer (LM / TPU) and the sensing electrode layer (PDA-Ag / spandex) are physically isolated by a hot melt adhesive interface layer, which avoids short circuits, signal drift and electrode corrosion caused by LM migration. At the same time, the hot melt adhesive layer acts as a stress buffer medium, so that the whole structure maintains its structural integrity in repeated stretching-releasing cycles.
[0040] (3) The preparation process is simple and does not require inert atmosphere, high temperature sintering or vacuum deposition. It only requires conventional ultrasonic, stirring, coating and hot pressing equipment. The raw materials are widely available (most polyphenols are natural extracts or industrial by-products), which meets the requirements of green manufacturing and low-cost large-scale production.
[0041] (4) Excellent comprehensive performance. The resulting laminated composite material has an electromagnetic shielding efficiency of 50 dB or more in the X-band, and the absorption coefficient A > R. After 1000 stretching cycles, the shielding and sensing performance retention rate is > 90%, which is suitable for wearable health monitoring, flexible electromagnetic protective clothing, intelligent sports equipment and other fields. Attached Figure Description
[0042] Figure 1This is a schematic diagram of the dispersion of liquid metal;
[0043] Figure 2 SEM images of undispersed liquid metal (a) and dispersed liquid metal (b);
[0044] Figure 3 SEM images of AgNPs chemically grown on the surface of spandex;
[0045] Figure 4 SEM images of liquid metal dispersed in TPU matrix (a) and liquid metal / TPU-spandex laminate composite material (b);
[0046] Figure 5 Electromagnetic shielding performance (a) and ART coefficient (b) of samples modified with different polyphenols;
[0047] Figure 6 Electromagnetic shielding performance (a) and ART coefficient (b) of samples with different liquid metals.
[0048] Figure 7 Electromagnetic shielding performance (a) and ART coefficient (b) of samples with different types of dispersed organic solvents.
[0049] Figure 8 This is a stability diagram for strain sensing. Detailed Implementation
[0050] The following examples further illustrate the above-described content of the present invention, but it should not be construed as limiting the scope of the subject matter of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention.
[0051] (I) The Influence of Different Polyphenols on the Dispersion of Liquid Metals and the Electromagnetic Shielding Behavior of Composite Materials
[0052] (S1) Preparation of stable and dispersed gallium-based liquid metal precursor solution
[0053] 10g of GaIn liquid metal was added to 100mL of N,N-dimethylformamide (DMF) solvent to prepare five portions, one with and one without 1g of gallic acid, lignin, dopamine, and tannic acid, respectively. The portions were then ultrasonically dispersed using a cell ultrasonic homogenizer (500 W, 50 min) to allow the polyphenols to react with GaIn. 3+ Chelating coordination and promoting gallium oxide shell formation yields a stable liquid metal dispersion;
[0054] (S2) Preparation of liquid metal / TPU film
[0055] The liquid metal dispersion prepared in S1 was mixed with thermoplastic polyurethane elastomer (TPU) masterbatch, including 20 mL of gallium-based liquid metal mixture and 8 g of TPU masterbatch. Organic solvent was added to make 4 mL. The mixture was stirred and dispersed at 80 °C for 30 min at a speed of 270 rpm / min. The mixture was then poured into a mold and shaped. After solvent evaporation, a liquid metal / TPU film with a thickness of 2 mm was obtained.
[0056] (S3) Preparation of LM / TPU elastic film
[0057] Dissolve 2 g of polydopamine hydrochloride in 1000 mL of deionized water, adjust the pH to 8.0 with 1 M NH3·H2O solution, and stir a 10 cm × 10 cm spandex fabric in this solution at room temperature for 17 h. Remove and dry at 60 °C for later use. Dissolve 1.5 g of AgNO3 in 120 mL of deionized water, add an appropriate amount of NH3·H2O solution until the solution changes from brown to transparent. After adding 2 g of glucose, soak the modified spandex fabric and stir magnetically for 60 min to form loaded AgNPs.
[0058] (S4) Laminated hot-pressed integrated
[0059] The liquid metal / TPU film prepared by S2 and the conductive modified spandex prepared by S3 were hot-pressed together through an intermediate hot melt adhesive layer. The hot-pressing temperature was 150 ℃, the pressure was 3 MPa, and the hot-pressing time was 5 min. After cooling, an integrated composite material was obtained.
[0060] The compositions of different polyphenol samples in Examples 1-4 and Comparative Example 1 are shown in Table 1. The electromagnetic shielding performance and sensing performance of the samples are shown in Tables 2-3, respectively.
[0061] Table 1: Composition of different polyphenol samples
[0062]
[0063] Table 2: Electromagnetic shielding performance of samples modified with different polyphenols
[0064]
[0065] Table 3: Sensing performance of samples modified with different polyphenols
[0066]
[0067] This invention first explores the effects of different polyphenolic substances on the dispersibility and electromagnetic absorption behavior of liquid metals. Under ultrasonic dispersion, polyphenol molecules (such as gallic acid and lignin) undergo strong chelation coordination with Ga2O3 generated on the surface of the liquid metal, forming a "gallium oxide / polyphenol" organic-inorganic composite shell on the particle surface (e.g., ...). Figure 1 (As shown). This core-shell structure provides strong steric hindrance and electrostatic repulsion, preventing the liquid metal (LM) from fusing into a large metal network. Instead, it remains as independent single particles uniformly suspended in the DMF solvent, allowing it to be uniformly dispersed within the TPU matrix (e.g., Figure 2 (as shown in b). The highly conductive spandex at the bottom layer was characterized by SEM (e.g., ...). Figure 3 As shown in the image, the surface of a single spandex fiber is rough and uniformly coated with silver particles, forming a continuous conductive network. This structure provides a good conductive foundation for subsequent high shielding performance. The liquid metal dispersion in the TPU matrix was characterized by SEM (e.g., ...). Figure 4 As shown in Figure a), the liquid metal is uniformly dispersed in the TPU matrix in the form of single particles. When it is hot-pressed and laminated with conductive spandex, the two are tightly bonded together (as shown in Figure a). Figure 4 (as shown in b).
[0068] The shielding performance of liquid metal / TPU-spandex laminated composites prepared with different polyphenol dispersions was tested. The overall electromagnetic shielding performance of the composites all reached 70 dB or higher (e.g., Figure 5 As shown in a). Further graphical analysis of its ART coefficients (e.g.) Figure 5 As shown in b), in Comparative Example 1, the reflectivity reached 0.9116. This is because the lack of polyphenol coating caused severe aggregation of LM, forming an uneven conductive network on the TPU surface, making it a reflective electromagnetic shielding material. Gallic acid, sodium lignosulfonate, and dopamine can efficiently react with Ga... 3+ Coordination forms small and uniformly distributed single particles, which are dispersed in the TPU matrix, creating an optimal impedance matching interface and achieving an absorption coefficient > 0.75, exhibiting high absorption characteristics. Example 4 uses tannic acid, with an absorption coefficient of 0.4076. Its absorption and shielding performance is inferior to the other three polyphenols. This may be because tannic acid has a large molecular weight and strong steric hindrance, making it difficult to form uniformly sized single particles, resulting in uneven micro-dispersion.
[0069] In Comparative Example 1, there was no strain sensing performance because there was no uniformly dispersed single-particle structure, and a reversible "change in interparticle distance / contact resistance" could not be formed during stretching, thus resulting in no strain sensing performance. However, by adding polyphenol-uniformly dispersed single-particle liquid metal, the tunneling distance and contact state between particles changed sensitively during the strain process. Examples 1 and 2 showed a wide detection range and high sensitivity (gallic acid GF = 6; lignin GF = 5.5). In Examples 3 and 4, the particle dispersion uniformity deteriorated, causing the effective conductive network of the sensor to be easily destroyed prematurely during the stretching process, narrowing the strain range (dopamine GF = 0-15%; tannic acid GF = 0-10%), and the sensitivity also decreased accordingly (dopamine GF = 4.67; tannic acid GF = 3).
[0070] (II) Influence of different liquid metal dispersion properties and their composite material electromagnetic shielding behavior
[0071] (S1) Preparation of stable and dispersed gallium-based liquid metal precursor solution
[0072] 10g each of gallium-indium alloy, gallium-tin alloy, and gallium-indium-tin alloy were added to 150 mL of THF solvent, along with 1.5g of lignin. The mixtures were then ultrasonically dispersed using a cell ultrasonic pulverizer (700 W, 20 min) to allow the polyphenols to react with the Ga... 3+ Chelating coordination and promoting gallium oxide shell formation yields a stable liquid metal dispersion;
[0073] (S2) Preparation of liquid metal / TPU film
[0074] The liquid metal dispersion prepared in S1 was mixed with thermoplastic polyurethane elastomer (TPU) masterbatch, with 15 mL of different liquid metal mixtures, 9 g of TPU masterbatch, and 12 mL of organic solvent added. The mixture was stirred and dispersed at 80 °C for 30 min at a speed of 270 rpm / min, and then poured into a mold to form a liquid metal / TPU film with a thickness of 2 mm after solvent evaporation.
[0075] (S3) Preparation of LM / TPU elastic film
[0076] Dissolve 3.5 g of polydopamine hydrochloride in 1000 mL of deionized water, adjust the pH to 9.0 with 1 M NH3·H2O solution, and stir a 10 cm × 10 cm spandex fabric in this solution at room temperature for 24 h. Remove and dry at 60 °C for later use. Dissolve 1 g of AgNO3 in 100 mL of deionized water, add an appropriate amount of NH3·H2O solution until the solution changes from brown to transparent. After adding 3 g of tartaric acid, soak the modified spandex fabric and stir magnetically for 40 min to form loaded AgNPs.
[0077] (S4) Laminated hot-pressed integrated
[0078] The liquid metal / TPU film prepared by S2 and the conductive modified spandex prepared by S3 were hot-pressed together through an intermediate hot melt adhesive layer. The hot-pressing temperature was 150 ℃, the pressure was 3 MPa, and the hot-pressing time was 5 min. After cooling, an integrated composite material was obtained.
[0079] The compositions of the different liquid metal samples in Examples 5-7 and Comparative Example 2 are shown in Table 4, and the electromagnetic shielding performance and sensing performance of the samples are shown in Tables 5-6, respectively.
[0080] Table 4: Composition of Different Liquid Metal Samples
[0081]
[0082] Table 5: Electromagnetic shielding performance of samples from different liquid metals
[0083]
[0084] Table 6: Sensing performance of samples modified with different liquid metals
[0085]
[0086] This invention further explores the effects of different types of liquid metals (gallium-indium alloy, gallium-tin alloy, and gallium-indium-tin alloy) on the dispersibility and electromagnetic absorption behavior of liquid metals. Under ultrasonic dispersion, lignin molecules undergo strong chelation coordination with Ga2O3 generated on the surfaces of different liquid metals, forming a "gallium oxide / lignin" organic-inorganic composite shell on the particle surface. This core-shell structure provides strong steric hindrance and electrostatic repulsion, preventing the liquid metal particles from agglomerating due to high surface tension, allowing them to suspend in the solvent as independent single particles and be uniformly dispersed in the TPU matrix.
[0087] The shielding performance of liquid metal / TPU-spandex laminated composites prepared with different liquid metal dispersions was tested. All samples achieved a total shielding behavior exceeding 70 dB, realizing highly efficient electromagnetic shielding (e.g., Figure 6 (As shown in a). Further graphical analysis of its absorption behavior (e.g.) Figure 6 As shown in b), in Comparative Example 2 (without liquid metal), electromagnetic shielding is provided solely by the bottom layer of silver spandex conductive fabric, with a reflection coefficient of 0.9488 and an absorption coefficient of only 0.0512, which is a typical reflective electromagnetic shielding material.
[0088] In Examples 5 (GaIn Alloy) and 7 (GaInTl Alloy), the indium-containing gallium-based metals, with their low melting point and good fluidity at room temperature, can synergize highly efficiently with lignin to form small and uniformly distributed single particles. This creates an optimal impedance-matching interface within the TPU matrix, achieving high absorption coefficients (GaIn Alloy A = 0.7485, GaInTl Alloy A = 0.7756), demonstrating excellent high absorption characteristics. The composite material prepared by dispersion in Example 6 (GaInTl Alloy) has an absorption coefficient of 0.3816 and a reflection coefficient as high as 0.6183, indicating significantly inferior absorption and shielding performance compared to the other two indium-containing liquid metals. This may be due to the poor interfacial tension and wettability of the GaInTl Alloy, resulting in insufficient coordination stability with lignin and difficulty in breaking it down into uniform and stable single particles under ultrasonication. This leads to localized agglomeration in the micro-regions, disrupting the electromagnetic impedance matching of the surface layer.
[0089] In Comparative Example 2, the material lacks strain-sensing properties because the TPU surface layer lacks a uniformly dispersed conductive phase, preventing the formation of a reversible "particle distance / contact resistance change" during stretching. However, by incorporating a uniformly dispersed single-particle structure of liquid metal, the tunneling distance and contact state between particles change sensitively during strain. Example 5 (gallium indium alloy) exhibits the widest detection range (0-25%) and the highest sensitivity (GF = 6.8); Example 7 (gallium indium tin alloy) also demonstrates excellent sensing response (detection range 0-20%, GF = 6.8).
[0090] Example 6 (Gallium-Tin Alloy): Due to the poor uniformity of particle dispersion, micro-area agglomeration is easily generated, which leads to the premature destruction of the effective conductive network of the sensor during the stretching process, narrowing the strain range (0-15%), and reducing the sensitivity accordingly (GF = 5.33).
[0091] (III) The Influence of the Type of Dispersing Organic Solvent on the Dispersibility of Liquid Metals and the Electromagnetic Shielding Behavior of Composite Materials
[0092] (S1) Preparation of stable and dispersed gallium-based liquid metal precursor solution
[0093] 20 g of GaIn liquid metal was added to 100 mL of deionized water, N,N-dimethylformamide (DMF), tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), and acetone solvents, respectively, along with 2 g of gallic acid. The mixture was then ultrasonically dispersed using a cell ultrasonic disruptor (600 W, 40 min) to allow the polyphenols to react with GaIn. 3+ Chelating coordination and promoting gallium oxide shell formation yields a stable liquid metal dispersion;
[0094] (S2) Preparation of liquid metal / TPU film
[0095] The liquid metal dispersion prepared in S1 was mixed with thermoplastic polyurethane elastomer (TPU) masterbatch, including 20 mL of gallium-based liquid metal mixture and 10 g of TPU masterbatch. Organic solvent was added to make 10 mL. The mixture was stirred and dispersed at 80 °C for 30 min at a speed of 270 rpm / min. The mixture was then poured into a mold and shaped. After solvent evaporation, a liquid metal / TPU film with a thickness of 2 mm was obtained.
[0096] (S3) Preparation of LM / TPU elastic film
[0097] 4 g of dopamine hydrochloride was dissolved in 1000 mL of deionized water, and the pH was adjusted to 8 with 1 M NH3·H2O solution. A 10 cm × 10 cm spandex fabric was stirred in this solution at room temperature for 15 h, then removed and dried at 60 °C for later use. 2 g of AgNO3 was dissolved in 100 mL of deionized water, and an appropriate amount of NH3·H2O solution was added until the solution changed from brown to transparent. After adding 3 g of tartaric acid, the modified spandex fabric was soaked and magnetically stirred for 40 min to form loaded AgNPs.
[0098] (S4) Laminated hot-pressed integrated
[0099] The liquid metal / TPU film prepared by S2 and the conductive modified spandex prepared by S3 were hot-pressed together through an intermediate hot melt adhesive layer. The hot-pressing temperature was 160 ℃, the pressure was 4 MPa, and the hot-pressing time was 6 min. After cooling, an integrated composite material was obtained.
[0100] The composition of samples with different types of dispersed organic solvents in Examples 8-11 and Comparative Example 3 is shown in Table 7. The electromagnetic shielding performance and sensing performance of the samples are shown in Tables 8-9, respectively.
[0101] Table 7: Composition of Samples with Different Dispersed Organic Solvents
[0102]
[0103] Table 8: Electromagnetic shielding performance of samples with different types of dispersed organic solvents
[0104]
[0105] Table 9: Sample Sensing Performance with Different Types of Dispersed Organic Solvents
[0106]
[0107] This invention further explores the influence of the type of dispersing organic solvent (deionized water, DMF, THF, DMSO, acetone) on the dispersibility and electromagnetic absorption behavior of liquid metals. Under ultrasonic dispersion, gallic acid undergoes strong chelation coordination with Ga2O3 generated on the surface of the liquid metal, forming a "gallium oxide / gallic acid" organic-inorganic composite shell on the particle surface. This core-shell structure provides strong steric hindrance and electrostatic repulsion, preventing the liquid metal from fusing into a large metal network, but instead suspending it as independent single particles in the dispersing solvent. The polarity and solubility of the solvent not only determine the dispersion effect of gallic acid, but also directly affect the compatibility of the liquid metal precursor with the TPU matrix and the film quality.
[0108] The shielding performance of liquid metal / TPU-spandex laminated composites prepared by dispersion in different solvents was tested. For overall shielding behavior, all achieved above 70 dB, demonstrating highly efficient electromagnetic shielding performance (e.g., Figure 7 (As shown in a). To further investigate the influence of the upper layer on its shielding behavior, its ART coefficient was plotted and analyzed. Its absorption coefficient A is greater than R in all cases, and A > 0.7 in all cases, indicating it is an absorptive electromagnetic shielding material (such as...). Figure 7 (As shown in b). Further analysis of the test results revealed that in Comparative Example 3 (deionized water), due to the hydrophobic nature of TPU, severe polar phase separation occurred between TPU and the aqueous phase, preventing LM particles from integrating into the TPU matrix and thus hindering film formation. Consequently, its shielding performance could not be tested. In Example 8, DMF, being both an excellent solvent for gallic acid and a superb solvent for TPU, enabled the gallic acid-coated LM particles to achieve optimal uniform dispersion, constructing an optimal impedance-matching interface within the TPU matrix. This resulted in an absorption coefficient as high as 0.8350 and a reflection coefficient as low as 0.1650, exhibiting outstanding high absorption characteristics. Examples 9, 10, and 11 all effectively dissolved TPU and dispersed gallic acid, and the resulting composite materials all exhibited excellent absorption characteristics (absorption coefficient > 0.7).
[0109] In Comparative Example 3, the material lacked strain sensing properties due to its inability to form a film. However, the system achieving uniform dispersion of single particles using an organic solvent exhibited sensitive changes in the tunneling distance and contact state between particles during strain. Example 8 demonstrated the widest detection range (0-25%), the highest relative resistance change, and high sensitivity (GF = 6.0). Further testing of its performance under a 10% cyclic tensile strain over 60 s was also demonstrated. Figure 8As shown, the signal is stable and has good signal repeatability. Example 9 also maintained high sensitivity (GF = 6.0, detection range 0-20%); however, due to the different solvent evaporation rates (slow evaporation of DMSO or rapid evaporation of acetone leading to slight differences in the distribution of local particle micro-regions), the sensing sensitivity of Examples 10 and 11 decreased slightly, with GF values of 5.5 and 5.0 respectively, and detection ranges of 0-20% for both.
[0110] Mechanism analysis
[0111] Based on the above structural design and experimental results, the liquid metal thermoplastic polyurethane-spandex laminated composite material constructed in this invention achieves a dual-function integration of high-efficiency absorption-type electromagnetic shielding and high-sensitivity tensile sensing. Under the coordination stabilization effect of polyphenols (such as gallic acid, lignin, and dopamine), the gallium-based liquid metal is modified into independent and uniformly dispersed single particles, avoiding agglomeration due to the high surface tension of the liquid metal. This allows it to disperse as individual particles within the TPU matrix, while simultaneously altering the large-size continuous conductive network formed by phase fusion. This isolated and dispersed microscopic phase prevents electromagnetic impedance mismatch on the material surface, enabling incident electromagnetic waves to penetrate the surface layer and enter the material interior without obstruction. The highly conductive spandex fabric loaded with silver nanoparticles (AgNPs) at the bottom layer has extremely high conductivity. When electromagnetic waves from the upper layer reach this interface, they are dissipated in the form of conductivity loss. At the same time, they return to the upper layer and dissipate electromagnetic wave energy in the form of interface polarization loss, dipole polarization loss, and conductivity loss. Overall, an efficient loss path of "absorption-reflection-reabsorption" is formed, which ultimately converts electromagnetic energy into heat energy for dissipation, achieving a high absorption coefficient and preparing an absorptive electromagnetic shielding material.
[0112] The tensile sensing properties of this composite material rely on the dynamic tunneling and contact resistance changes between isolated LM microparticles within the TPU elastic matrix. Under normal conditions, the LM microparticles, uniformly dispersed within the TPU elastic matrix, are close to each other, separated by thin shells and polymer chain segments, forming an initial three-dimensional conductive network based on quantum tunneling and weak contact, maintaining a low initial resistance. When the composite material is subjected to axial tensile strain, the TPU matrix undergoes tensile deformation, driving the embedded LM individual particles to undergo relative displacement and slippage along the tensile direction, increasing the average distance between particles. As the strain further increases, the initially weakly contacting particle pairs separate, reducing the effective conductive pathway and resulting in a change in relative resistance. After the external force is removed, the elastic restoring force of the TPU polymer chains pushes the LM particles back together and resets, allowing the conductive network to be fully reconstructed, and the resistance to return to its initial state. It is this highly reversible and highly sensitive microscopic geometric network evolution, based on the uniform dispersion of individual particles, that enables the material to exhibit tensile sensing properties.
Claims
1. A method for preparing a liquid metal thermoplastic polyurethane-spandex laminated composite material, characterized in that... Includes the following steps: S1. A gallium-based liquid metal and polyphenols containing catechol and / or trihydroxyl groups are ultrasonically dispersed in an organic solvent, allowing the polyphenols to react with the Ga... 3+ Chelating coordination and promoting gallium oxide shell formation yields a stable liquid metal dispersion; The polyphenolic substances are one or more of gallic acid, lignin, dopamine, or tannic acid; The gallium-based liquid metal is one or more of gallium-indium alloy, gallium-indium-tin alloy, or gallium-tin alloy; The organic solvent is one or more of N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide, acetone, or butanone; S2. Stir and mix the liquid metal dispersion with the thermoplastic polyurethane elastomer (TPU) masterbatch until uniform, pour into a mold to form a liquid metal / TPU film; S3. Construct an adhesive layer containing catechol groups on the surface of spandex, and then place it in a solution containing silver ions to in-situ reduce and deposit silver nanoparticles to obtain conductive modified spandex. S4. The liquid metal / TPU film is hot-pressed together with conductive modified spandex to form an integrated liquid metal thermoplastic polyurethane-spandex laminated composite material.
2. The preparation method according to claim 1, characterized in that: In S1, The polyphenolic substance is one or more of gallic acid and lignin; The gallium-based liquid metal is one or more of gallium-indium alloy or gallium-indium-tin alloy; The organic solvent is one or more of N,N-dimethylformamide, tetrahydrofuran, or butanone.
3. The preparation method according to claim 1 or 2, characterized in that: In S1, The mass of the polyphenolic substance is 1-10% of the mass of the gallium-based liquid metal. The mass ratio of the gallium-based liquid metal to the organic solvent is 1:100 to 20:
100.
4. The preparation method according to claim 1 or 2, characterized in that: In S1, the ultrasonic pulverization is performed using a cell ultrasonic pulverizer with an ultrasonic power of 300-700 W and an ultrasonic time of 30-80 min.
5. The preparation method according to claim 1, characterized in that: In S2, the gallium-based liquid metal accounts for 1-10% of the mass of the thermoplastic polyurethane elastomer (TPU) masterbatch, and organic solvent is added to make the total solvent amount 2-4 times the mass of the thermoplastic polyurethane elastomer (TPU) masterbatch.
6. The preparation method according to claim 1 or 5, characterized in that: In S2, The stirring temperature is 70-90℃, and the stirring time is 10-60 min; The thickness of the liquid metal / TPU film is 1-3 mm.
7. The preparation method according to claim 1, characterized in that: In S3, the adhesive layer containing catechol groups is formed by the oxidative self-polymerization of dopamine hydrochloride in Tris buffer at pH 8.0-9.0, with a dopamine concentration of 1-4 mg / mL and a reaction time of 12-24 h at room temperature.
8. The preparation method according to claim 1 or 7, characterized in that: In S3, The silver ion-containing solution is a silver ammonia solution with a concentration of 0.05-0.5 mol / L and an in-situ reduction deposition time of 10-60 min; or the silver ion-containing solution is an AgNO3 complexation system solution with organic acid. The reducing agent used is one of glucose, ascorbic acid, or tartaric acid.
9. The preparation method according to claim 1, characterized in that: In S4, the liquid metal / TPU film and the conductive modified spandex are hot-pressed together through an intermediate hot melt adhesive layer; the hot melt adhesive layer is an EVA hot melt adhesive film or a polyurethane hot melt adhesive film with a thickness of 0.05-0.2 mm; the hot pressing temperature is 120-180 ℃, the pressure is 0.5-5 MPa, and the hot pressing time is 1-10 min.
10. A liquid metal thermoplastic polyurethane-spandex laminated composite material prepared by the preparation method according to any one of claims 1-9.